Increasing family planning in Myanmar: the role of the private sector and social franchise programs - Tin Aung; Nang Mo Hom; May Sudhinaraset (BMC, 2017)
Abstract Background This study examines the influence of clinical social franchise program on modern contraceptive use. Methods This was a cross-sectional survey of contraceptive use among 2390 currently married women across 25 townships in Myanmar in 2014. Social franchise program measures were from programmatic records. Results Multivariable models show that women who lived in communities with at least 1-5 years of a clinical social franchise intrauterine device (IUD) program had 4.770 higher odds of using a modern contraceptive method compared to women living in communities with no IUD program [CI: 3.739-6.084]. Townships where the reproductive health program had existed for at least 10 years had 1.428 higher odds of reporting modern method use compared to women living in townships where the programs had existed for less than 10 years [CI: 1.016-2.008]. Conclusions This study found consistent and robust evidence for an increase in family planning methods over program duration as well as intensity of social franchise programs.